Preclinical Assessment of Safety and Efficacy of Fluorescent Dye for Detecting Dermal Injuries (the injuries were both abrasions and incision) in a Murine Model1. Issue 6 (8th August 2016) - Bruce, Anthony C.; Cao, Yiqi; Henry, Catherine; Peirce, Shayn M.; Laughon, Kathryn
Abstract: Objective documentation of tears and abrasions to the external genitalia after sexual assault is an important part of the forensic examination. A 1% aqueous solution of toluidine blue (TB) dye is often used to highlight injury, but the dye can be difficult to see on dark skin. We evaluated a fluorescent dye for detecting injuries on all skin colors in a relevant preclinical murine model. We compared the ability of trained, blinded observers to detect unstained wounds and wounds stained with 1% fluorescein sodium (FL) and with TB. We also evaluated the cutaneous wound healing response after application of both dyes. The no‐dye group had significantly fewer ( p < 0.05) true‐positive identifications compared to all the dye groups. No differences in effectiveness were detected between dye treatments. All groups exhibited statistically similar healing rates. These findings support the evaluation of fluorescein sodium in a future clinical study with human subjects.